1998
DOI: 10.1088/0268-1242/13/6/013
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence and nature of lightly spark-processed silicon

Abstract: We report the emission of significant infra-red as well as visible electroluminescence (EL) from lightly spark-processed Si (LSP-Si). Studies by scanning tunnelling microscopy (STM) reveal the presence of small globules down to around 2 nm in diameter, the sizes necessary for significant quantum confinement and blue-shifted interband radiation to occur. However, studies with oxidized samples and samples processed in non-oxygen gases suggest that silicon oxides play a major role. Measurements by elastic recoil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…In the case of lightly SP-Si, our recent studies 12 indicate that the spectrum of EL is similar to that in Fig. 5, with a peak at above 650 nm, together with stronger infrared radiation peaked at the Si band gap.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the case of lightly SP-Si, our recent studies 12 indicate that the spectrum of EL is similar to that in Fig. 5, with a peak at above 650 nm, together with stronger infrared radiation peaked at the Si band gap.…”
Section: Discussionsupporting
confidence: 70%
“…10 In the cases of por-Si ͑Ref. 12͒ and SP-Si, 12 there is evidence for the presence of nanoparticles, so that quantum-confinement hypotheses for explaining both the blueshift and the enhanced emission intensity are possible.…”
Section: Introductionmentioning
confidence: 99%
“…6 This visible EL is also similar to that from lightly spark processed Si, mechanically damaged SiO 2 /Si, and laser-grooved Si. [10][11][12] Similar experiments on a p-type sample with native oxide gave similar emission, but EL only occurred under forward biased conditions. This is to say that in p and n cases, for visible EL to occur, the top metal electrode must be negatively biased, i.e., electrons must be injected into the Si wafer from the metal electrode.…”
Section: And D Haneman A)mentioning
confidence: 54%
“…Other investigators [2] using conventional sp found EL spectra, which appear to peak near 950 nm (1.31 eV), 775 nm (1.6 eV) and 650 nm (1.9 eV) when utilizing a few selected optical filters instead of a continuous spectrometer, as we did. In a later paper the same investigators [4] moved the 950 nm peak to 1150 nm (1.1 eV) .…”
Section: Methodsmentioning
confidence: 99%